Advances in the study of internal solitary waves and their interaction with marine structures - Peng DU; Pingyu SUN; Miao ZHANG; Qinghui ZHANG; Mengge SUN; Haibao HU; Xiaopeng CHEN (Zhongguo Jianchuan Yanjiu)
Internal solitary waves (ISWs) are a common nonlinear, large-amplitude fluctuation phenomenon which is widely present in densely stratified oceans and can induce the shear state of the seawater flow above and below the wave surface during the propagation process, causing strong amplitude dispersion and the sudden strong flow of seawater. When a moving submersible operates underwater, it is very likely to encounter ISWs. The motion stability and hydrodynamic load characteristics of the submersible are seriously affected by the peak and valley depths and energy concentrations of ISWs, which in turn leads to its unstable motion and uncontrolled maneuvering. Based on the engineering background of the interaction between ISWs in the ocean and underwater submersibles, this paper summarizes current research on the characteristics of ISWs in terms of theory, numerical simulation and observation and experiment. Studies on the interaction between ISWs and marine structures and submersibles are then highlighted. Finally, based on the current status of ISW research at home and abroad, the future prospects of ISW research are further proposed.